2017
DOI: 10.1177/0954407017728633
|View full text |Cite
|
Sign up to set email alerts
|

Design of electromechanical height adjustable suspension

Abstract: In the general context of vehicles' fuel consumption and emissions reduction, the minimization of the aerodynamic drag can offer not negligible benefits regarding the environmental issues. The adjustment of the vehicle height is one of the possible ways to provide a reduction of the resistances to vehicle motion, in addition to consequent aspects regarding the increased versatility of the vehicle. The aim of this paper is to present in a systematic way to the state of the art of height adjustment systems for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Considering that the corporate average emission level of most vehicle manufacturers is around 120 gCO 2 /km, researchers and engineers must deal with technologies that push emissions to lower limits. In this regard, height adjustable suspensions offer notable benefits with regard to fuel consumption and emission reduction and improved comfort for a reasonable cost [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that the corporate average emission level of most vehicle manufacturers is around 120 gCO 2 /km, researchers and engineers must deal with technologies that push emissions to lower limits. In this regard, height adjustable suspensions offer notable benefits with regard to fuel consumption and emission reduction and improved comfort for a reasonable cost [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Amati et al [11] have performed a detailed analysis of height adjustment suspensions. They developed two electromechanical height adjustment prototypes and demonstrated that the vehicle fuel consumption for an average class A vehicle can be reduced consequently as a result of aerodynamic drag force reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New ambitious targets on the amount of CO 2 emissions set by European Commission [1,2] require implementation of even more efficient technologies from car manufacturers. Since the last decade of the 20th century, a wide variety of different technologies and policies aiming the reduction of vehicle fuel consumption and emissions at different vehicle and infrastructure level are widely implemented [3,4]. Most regulations in the past were focused on the reduction of the pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Vehicle height adjustment can improve vehicle handling stability and passing ability on bad road [1,2]. The vehicle height control is mainly based on active suspension, and the adopted actuators are mainly air suspension and hydraulic suspension [3,4], which have the problems such as large energy consumption, high cost, complex structure, and slow response [5][6][7]. In addition, the vehicle shifting system based on active suspension requires the installation of additional vehicle shifting devices, and the structure is very complex, for example, the vehicle height adjustment system based on air suspension inflates and deflates the air on the spring through the air pump to change the vehicle body height, and the system requires additional components such as an air pump, an air storage tank, and an air filling and deflating line [8,9].…”
Section: Introductionmentioning
confidence: 99%